Mechanical and self‐sensing properties of 3D printed continuous carbon fiber reinforced composites. Issue 10 (14th July 2022) - Ye, Wenguang; Dou, Hao; Cheng, Yunyong; Zhang, Dinghua; Lin, Sheng
Abstract: The additive manufacturing technology of continuous carbon fiber reinforced composites (CCFRCs) based on fused filament fabrication offers new opportunities for the preparation and application of composites. This study prepared CCFRCs with excellent mechanical properties based on 3D printing technology. At the same time, a stress–strain and damage sensing method for the CCFRCs is proposed. Research results show that the maximum tensile stress and tensile modulus of 3D printed CCFRCs are 3.36 times and 5.10 times that of PLA, while the maximum flexural stress and flexural modulus are 3.24 times and 4.90 times that of PLA. Furthermore, the stress–strain and damage of CCFRCs strongly correlate with the resistance change in 3D printed structures. The state of the CCFRCs can be sensed by the change of resistance in the structure. Finally, the application potential of 3D printed CCFRCs self‐sensing specimens in action recognition of finger joints was discussed through experiments. Abstract :